Contaminated Urban Soils - Meuser, Helmut. (Environmental Pollution, 2010)
This book gives a current overview of all facets of urban soils. Different urban land-use types in a number of examples worldwide are introduced. Many examples in different countries are provided in order to illustrate the situation in detail. The contaminant sources of urban soils (e.g., dust deposition, contamination along roadsides, contamination of floodplains, application of wastewater, anthropogenic deposits) are comprehensively presented. For practical application purposes a key with which to identify technogenic materials during field work is presented. Features like reductomorphic conditions in landfill soils, acidification of coal mining heaps and the impact of physical characteristics such as sealing are taken into consideration in the context of the contamination problem. The mobility of contaminants in the soils under consideration is introduced and discussed. The content of the book, however, is not limited to the description of contaminated urban soils. Different methods of assessment (classification, functional assessment, assessment focused on pathways with reference to standardized exposure scenarios) are introduced. Finally, quality standards for contaminated land in a number of countries are listed, compared and discussed. The book links up the contamination problem of urban soils with geographical aspects such as the historical development of city growth, the process of urbanization and the urban-to-rural gradients. Accordingly, the reader will be able to understand the specific problems of contaminated urban soils and will find sensible approaches to assessment.